1998
DOI: 10.2307/3546481
|View full text |Cite
|
Sign up to set email alerts
|

The Balance between Positive and Negative Plant Interactions and Its Relationship to Environmental Gradients: A Model

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..Wiley-Blackwell and Nordic Society Oikos are collaborating with JSTOR to digitize, preserve and extend access to Oikos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
521
9
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 587 publications
(591 citation statements)
references
References 46 publications
56
521
9
5
Order By: Relevance
“…Moreover, the previous study on alpine neighboring plant species suggested that competition interaction generally, but not exclusively, dominated at lower elevations, and facilitation interactions among plants were predominant at high elevations, which was due to the different degree of physically stressful conditions [20]. As the results in this work, some new evidences were developed from a molecular methodological insight regarding the hypothesis that the relative importance of facilitation and competition varies inversely along gradients of abiotic stress [52]. Overall, facilitation rather than competition may play a more predominant role in the earlier stages of BSCs phototroph communities under harsher conditions.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, the previous study on alpine neighboring plant species suggested that competition interaction generally, but not exclusively, dominated at lower elevations, and facilitation interactions among plants were predominant at high elevations, which was due to the different degree of physically stressful conditions [20]. As the results in this work, some new evidences were developed from a molecular methodological insight regarding the hypothesis that the relative importance of facilitation and competition varies inversely along gradients of abiotic stress [52]. Overall, facilitation rather than competition may play a more predominant role in the earlier stages of BSCs phototroph communities under harsher conditions.…”
Section: Discussionmentioning
confidence: 55%
“…hermaphroditum at higher altitude sites under harsh conditions (as predicted by the stress-gradient hypothesis; (Bertness and Callaway 1994;Brooker and Callaghan 1998). Alternatively, the relationship does not necessarily represent direct facilitation between E. hermaphroditum and lichens, but indirect effect of E. hermaphroditum outcompeting vascular plant species, thus creating habitat patches more suitable for lichens due to less intense competition for light and space from taller vascular species.…”
Section: Resultsmentioning
confidence: 95%
“…It has been suggested that the nature of interactions may shift from positive, under environmentally stressful conditions, to neutral, and eventually become negative with decreasing stresses (Bertness & Callaway 1994, Callaway & Walker 1997, Brooker & Callaghan 1998. Indeed, some previous studies have indicated such shifts on different spatial scales (e.g.…”
Section: Introductionmentioning
confidence: 99%